PERAN TEKNOLOGI INFORMASI DALAM AKTIFITAS DAKWAH: Menelusuri Signifikansi Dakwah Online - Rusli Rusli (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
This paper deals with the role of information technology in da'wa acivities. It concludes that because of the spread of Internet, online da'wa as a kind of new model of Islamic preaching emerges. This kind of da'wa focused on the socialization that includes process of al-ta'aruf (acquaintance) and al-ta'aluf (harmony) with the target of object of Islamic preaching ( al-mad' u). This is carried out based on the three levels of online interaction, which includes spreading, participation and mobilization.